2018
DOI: 10.4049/jimmunol.1701420
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef Disrupts CD4+ T Lymphocyte Polarity, Extravasation, and Homing to Lymph Nodes via Its Nef-Associated Kinase Complex Interface

Abstract: This work was supported by Deutsche Forschungsgemeinschaft Grants FA378/10-2 and SFB1129 (to O.T.F.) and SFB1129 (to M.T.), and the Nakatani Foundation (to M.T.). N. Tsopoulidis was supported by a Heidelberg Biosciences International Graduate School fellowship. O.T.F. and M.T. are members of the CellNetworks Cluster of Excellence (EXO81). O.T.F. designed the study, interpreted results, and wrote the manuscript together with B.S. M.L.-M. conducted and analyzed the experiments shown in Figs. 1-3 and 5. S.K. cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 84 publications
(124 reference statements)
3
12
0
Order By: Relevance
“…Immunofluorescence. T cell polarization was monitored by changes in cell morphology and the formation of uropods, as described previously (53). In brief, stimulatory coverslips (CSs) were prepared by coating with fibronectin (45 g/ml; Sigma-Aldrich) for 1.5 h. A total of 1 ϫ 10 7 A3.01 T cells per sample were electroporated as described above, harvested at 24 h posttransfection, resuspended in 100 l supplemented RPMI, seeded onto CSs, and allowed to polarize for 2 h at 37°C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence. T cell polarization was monitored by changes in cell morphology and the formation of uropods, as described previously (53). In brief, stimulatory coverslips (CSs) were prepared by coating with fibronectin (45 g/ml; Sigma-Aldrich) for 1.5 h. A total of 1 ϫ 10 7 A3.01 T cells per sample were electroporated as described above, harvested at 24 h posttransfection, resuspended in 100 l supplemented RPMI, seeded onto CSs, and allowed to polarize for 2 h at 37°C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the NAKC was shown to enhance the secretion of extracellular vesicles (EVs) containing Nef but also proinflammatory cytokines such as tumor necrosis factor alpha (TNF-␣) (48)(49)(50). In addition, deletions of this protein interaction site in HIV-1 Nef were shown to prevent downregulation of cell surface CD4 and MHC-I, antagonism of SERINC5, as well as disruption of CD4 T cell polarity and homing to lymph nodes (51)(52)(53). Beyond the demonstration of its overall relevance, which is based on a Nef mutant in which the entire stretch of residues from positions 12 to 39 are deleted (Δ12-39), this multifunctional N-terminal interaction site in HIV-1 Nef is less characterized, and we therefore set forth to define specific residues that mediate different activities of this region.…”
mentioning
confidence: 99%
“…They showed that actin molecules polymerize to resist pressure during centrifugation, which activates the cofilin protein leading to the depolymerization of actin filaments. The dynamic between actin and caffeine is required for T cell infection by HIV-1, which is altered by proteins such as gp120 and Nef [ 17 , 19 ]. In addition, spinoculation may induce chromatin remodeling and facilitate the entry of HIV-DNA into the genome of the infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression plasmids for pSTITCH‐GFP, pHit60, pHit123, and MLV‐A were kindly provided by Reno Debets (Department of Medical Oncology, Erasmus MC, Rotterdam, The Netherlands). The cloning strategy to insert NEF SF2 and various mutants in pSTITCH has been described (Stolp et al , 2012; Lamas‐Murua et al , 2018). The coding sequences for NEF SF2 A32‐39, NEF SF2 LLAA, or patient‐derived nef genes C122 and CB76 were cloned into pSTITCH using the restriction sites AgeI and PacI in a multiple‐cloning site that was previously subcloned along with IRES∆NGFR from pQCXIX backbone.…”
Section: Methodsmentioning
confidence: 99%